Association Study between the Polymorphisms of Matrix Metalloproteinase (MMP) Genes and Idiopathic Recurrent Pregnancy Loss - Park, Han Sung (Genes (Basel), 2019)
Recurrent pregnancy loss (RPL) refers to two or more consecutive pregnancy losses. It is estimated that fewer than 5% of women experience RPL. Matrix metalloproteinases (MMPs) are a family of proteolytic enzymes that play important roles in providing a safe and conducive environment for the stable development of the fetus. In this case-control study, we evaluated the associations between RPL and single nucleotide polymorphisms (SNPs) in MMP-8 and MMP-27. We recruited 375 Korean women with a history of RPL and 240 ethnically-matched healthy parous controls, and we performed genotyping for the MMP-8 rs2509013 C>T, MMP-8 rs11225395 G>A, and MMP-27 rs3809017 T>C polymorphisms. All SNPs were genotyped via the polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) assay. In the genotype frequency analyses, the TT genotype of the MMP-8 rs2509013 C>T (age-adjusted odds ratio, 0.415; 95% confidence interval, 0.257–0.671; P = 0.0003) and TC genotype of MMP-27 rs3809017 T>C (age-adjusted odds ratio, 0.681; 95% confidence interval, 0.483–0.961; P = 0.029) were associated with decreased RPL susceptibility. Moreover, these trends were maintained in the haplotype and genotype combination analyses. Interestingly, amongst the RPL patients, higher levels of homocysteine (P = 0.042) and uric acid (P = 0.046) were associated with MMP-27 rs3809017 T>C. In conclusion, the two polymorphisms of MMP-8 and MMP-27 were significantly associated with RPL risk, both individually and in combination. Therefore, these two polymorphisms are potential biomarkers for RPL susceptibility.